Spessi : Bensín. - Corbijn, Anton; Nahas, Dominique; Proppé, Jón; Thorláksson, Eirlkur; Reykjavik Art Museum, Reykjavik (Reykjavik : Reykjavik Art Museum, 1999)
Spessi's series Bensin (the word means gasoline in Iceland) features 113 photographs of gasoline stations, some of them located deep inside the Icelandic countryside.
biog., ind. tent., gr. tent., prijzen p. 116
Engels
IJslands
Spessi : Bensín, Reykjavik Art Museum, Reykjavik, mars - mai 1999
boek
Keywords: Spessi; Hallbjörnsson, Sigurbór; IJsland